« Combattre les perversions morales qui les ont poussées au mal » : la prise en charge de la déviance féminine par le tribunal pour mineurs de Valence (Espagne, 1939-1958) - Amélie Nuq (Les Cahiers de Framespa)
Through a case study focusing on the Valencian Juvenile Court and the Colonia San Vicente Ferrer, a reformatory school whose particularity was to house boys and girls in two different sections, we mean to put into relief some characteristics of the way female deviance was dealt with under Franco. The grounds to send boys and girls to reformatory schools were different. Judicial authorities and families were above all concerned with the moral and sexual aspects of female misconduct. Religion and work were meant to reform those “fallen” young women, mostly from popular backgrounds, in order to shape them into Christian mothers and spouses, in conformity with the female archetype glorified by the Francoist dictatorship.